Several comments on a Genizah fragment of Bavli, Eruvin 57B–59A - Zur, Uri (HTS teologiese studies, 2019)
This article refers to a Cairo Genizah fragment related to Bavli, Eruvin tractate 57b–59a, identified as Cambridge, UL T-S F1 (1) 85. FGP No. C 96541. The article begins with a description of the Genizah fragment and presents a reproduction of the fragment itself at the end of the article. Reference is made to the content and several comments are made in an effort to characterise the fragment.